2015
DOI: 10.1139/cjpp-2014-0415
|View full text |Cite
|
Sign up to set email alerts
|

Protective effects of polyethylene oxide on the vascular and organ function of rats with severe hemorrhagic shock

Abstract: This study examined the effects of polyethylene oxide (PEO) on the survival rate, hemodynamics, blood gas indexes, lactic acid levels, microcirculation, and inflammatory cytokine levels in rats subjected to severe hemorrhagic shock. The shocked rats were resuscitated with either Ringer's lactate solution or 20 ppm of PEO in Ringer's lactate solution for 1 h. It was found that infusion of PEO effectively improved the survival, metabolic acidosis, oxygen delivery, hyperlactacidemia, tissue perfusion, and inflamm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…Specifically, DRPs can improve tissue oxygenation and oxygen consumption in rats subjected to severe hemorrhagic shock [ 123 , 124 , 125 ]. Recently, Li et al pointed out that polyethylene oxide, one of the well-known water-soluble DRPs dissolved in Ringer’s acetate, can protect the kidneys against renal injury and functional loss along with the improvement in tissue perfusion and oxygen delivery and reducing lactic acid, creatinine, TNF-α and IL-6 [ 126 ]. It was concluded that, HS-related microcirculatory derangements in the kidney required more attention to improve not only systemic hemodynamics but also renal microcirculation: perfusion, oxygenation, and endothelial function by oxygen carriers (blood or HBOCs) and anti-inflammatory and antioxidant mediators ( Table 1 ).…”
Section: Microcirculatory Alterations During Akimentioning
confidence: 99%
“…Specifically, DRPs can improve tissue oxygenation and oxygen consumption in rats subjected to severe hemorrhagic shock [ 123 , 124 , 125 ]. Recently, Li et al pointed out that polyethylene oxide, one of the well-known water-soluble DRPs dissolved in Ringer’s acetate, can protect the kidneys against renal injury and functional loss along with the improvement in tissue perfusion and oxygen delivery and reducing lactic acid, creatinine, TNF-α and IL-6 [ 126 ]. It was concluded that, HS-related microcirculatory derangements in the kidney required more attention to improve not only systemic hemodynamics but also renal microcirculation: perfusion, oxygenation, and endothelial function by oxygen carriers (blood or HBOCs) and anti-inflammatory and antioxidant mediators ( Table 1 ).…”
Section: Microcirculatory Alterations During Akimentioning
confidence: 99%